2020
DOI: 10.3389/fmicb.2020.00252
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of Mating Type A1 and Indication of Epigenetic Effects During Early Stages of Mating in Phytophthora infestans

Abstract: The potato late blight pathogen Phytophthora infestans has both an asexual and a sexual mode of reproduction. In Scandinavia, the pathogen is reproducing sexually on a regular basis, whereas clonal lineages dominate in other geographical regions. This study aimed at elucidating events or key genes underlying this difference in sexual behavior. First, the transcriptomes of eight strains, known as either clonal or sexual, were compared during early stages of mating. Principal component analysis (PCA) divided the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…During mating of 10 different European P. infestans strain combinations, gene ontology analysis of transcriptome datasets showed significant enrichment of transferase activity, including the induced expression of eight acetyltransferases in strains and mating samples (Tzelepis et al, 2020). Since the authors only refer to these proteins as enzymes with putative acetyltransferase activity (Tzelepis et al, 2020), we looked for more specific HATs conserved domains and found that six of the reported proteins carry putative HATs domains. Both mating types of P. infestans (A1 and A2) are spread throughout Europe, increasing mating and leading to high genetic variability and more difficulties in controlling this pathogen (Heremans and Haesaert, 2004;Brurberg et al, 2011;Li et al, 2012;Runno-Paurson et al, 2016).…”
Section: Histone Acetylationmentioning
confidence: 99%
See 4 more Smart Citations
“…During mating of 10 different European P. infestans strain combinations, gene ontology analysis of transcriptome datasets showed significant enrichment of transferase activity, including the induced expression of eight acetyltransferases in strains and mating samples (Tzelepis et al, 2020). Since the authors only refer to these proteins as enzymes with putative acetyltransferase activity (Tzelepis et al, 2020), we looked for more specific HATs conserved domains and found that six of the reported proteins carry putative HATs domains. Both mating types of P. infestans (A1 and A2) are spread throughout Europe, increasing mating and leading to high genetic variability and more difficulties in controlling this pathogen (Heremans and Haesaert, 2004;Brurberg et al, 2011;Li et al, 2012;Runno-Paurson et al, 2016).…”
Section: Histone Acetylationmentioning
confidence: 99%
“…Furthermore, the epigenetic regulation of P. infestans sexual reproduction was recently proposed (Tzelepis et al, 2020). During mating of 10 different European P. infestans strain combinations, gene ontology analysis of transcriptome datasets showed significant enrichment of transferase activity, including the induced expression of eight acetyltransferases in strains and mating samples (Tzelepis et al, 2020).…”
Section: Histone Acetylationmentioning
confidence: 99%
See 3 more Smart Citations